Limbic encephalitis and bipolar affective disorder: a slow awakening. Issue 1 (22nd February 2018) - Lilford, Philippa; Morrison, Hamish; Morgan, Elsa; Ward, Rosalind
Abstract : There is increasing evidence for the role of autoimmune encephalitis in the aetiology of psychosis. Here, Dr Lilford and colleagues describe the case of a 74‐year‐old lady who presented as hypomanic almost a year previously and then developed bizarre stereotyped movements, periods of absences and became confused. She was admitted to an old age psychiatric ward and was then subsequently diagnosed with non‐paraneoplastic limbic encephalitis with high levels of voltage‐gated potassium channel complex antibodies. The authors discuss her treatment with immunosuppressive drugs, which resulted in significant clinical improvement.